The Determinants and Informativeness of Non-GAAP Revenue Disclosures - Campbell, John L.; Gee, Kurt H.; Wiebe, Zac (The Accounting Review, 2022)
ABSTRACT Most research on non-GAAP financial measures focuses on earnings or earnings per share, although non-GAAP revenue disclosure has recently attracted SEC scrutiny. It is unclear ex ante what non-GAAP adjustments could improve revenue's usefulness because, unlike earnings, revenue is a top-line number related primarily to core (i.e., persistent) business activities. We present the first archival analysis of non-GAAP revenues using a large, hand-collected sample of disclosures from 2015 to 2018. Approximately one in five earnings announcements contains a non-GAAP revenue disclosure, focused on revenue growth. Our evidence suggests that firms disclose non-GAAP revenue when GAAP revenue is incomparable with prior periods, and not to compensate for poor GAAP performance. Furthermore, non-GAAP revenue growth predicts future revenue growth better than GAAP revenue growth, and the market responds to this information. Overall, non-GAAP revenue disclosures are motivated by economic fundamentals rather than opportunism, on average, and they provide investors with relevant information.